Eksistensi Museum Benteng Vredeburg Sebagai Sarana Pendidikan Nasionalisme - Dikarsa, Asep Anggi; Nurrohimah, Annisa; Ardani, Nopita; Oktavia, Via Nur; Zulkarnaen, Barru Azizu (CV. Kurnia Grup, 2024)
Extraordinary crisis of morality along with the development and progress of the times. So understanding the historical values of struggle, especially nationalism, is important. The former Fort Vredeburg building was not intended for the purpose of preserving a symbol of Dutch colonial might and glory, but was directed to obtain a new function that could provide information and aspirations of the national struggle for future generations. For this reason, the Fort Vredeburg building is used as a museum of the National Struggle which is unique and second to none in Indonesia, so this research was conducted to determine the existence of the Fort Vredeburg Museum in Yogyakarta as a means of nationalist education. This research is qualitative research using literature study methods from various sources. Data collection was carried out through observation and interviews. The results of the research are: first, Understanding Nationalism of PPKn IPI Garut Students After a Visit to the Fort Vredeburg Museum. This proves that a visit to the Fort Vredeburg Museum can provide students with an understanding of nationalism by being able to enrich information. Second, the use of the Vredeburg Fort Museum Gallery as a means of nationalist education. This means that the Museum Gallery can provide nationalist education with interesting visualizations.